PENGARUH KELEMBABAN, SUHU, ARAH DAN KECEPATAN ANGIN TERHADAP KONSENTRASI KARBON MONOKSIDA (CO) DENGAN MEMBANDINGKAN DUA VOLUME SUMBER PENCEMAR DI AREA PABRIK DAN DI PERSIMPANGAN JALAN (Studi Kasus: PT. Inti General Yaja Steel dan Persimpangan Jrakah) - Faradina Arifiyanti (Jurnal Teknik Lingkungan, 2013)
The production process activities by steel smelting factory and transportation activities can generate carbon monoxide (CO) gaseous that dangerous. PT. Inti General Yaja Steel Semarang located at the intersection of Jrakah is one of steel smelting industry which uses the MFO as fuel for their production activities. The volume of fuel MFO used for by PT. Inti General Yaja Steel Semarang production and the volume of vehicles passing through Jrakah intersection  are the source of carbon monoxide (CO) which the dispersion process is affected by humidity, temperature, wind direction and speed. This study aim is to determine the effect of the pollutant sources volume, humidity, temperature, wind direction and speed on the concentration of CO in the area of the factory PT. Inti General Yaja Steel  and at the Jrakah intersection, besides, to determine whether the concentration of CO is mutually influenced by conditions in these two places.The research was conducted at vehicle crowded hours, normal factory production hours and non- production factory hours . Based on these results, the concentration of CO in the factory area range in value from 2 to 2.75 ppm at both vehicle crowded hours, normal production at the factory hours and non- production factory hours. The concentration of CO at the Jrakah intersection in vehicle crowded hours (7:00 to 8:00) are in range of 1.75 ppm - 30.25 ppm, the concentration of CO at Jrakah intersection in normal production hours (15:00 p.m. to 16:00) were between 11.25 ppm - 22.25 ppm, and the concentration of CO at Jrakah intersection in non-production hours (19:00 to 20:00) were in the range 4.5 ppm - 22.25 ppm.The statistic results indicate that there are significant differences in the concentrations of CO results in the factory area and at the Jrakah intersection. CO concentration in factory area is not affected by the volume of fuel, humidity, temperature, wind speed and direction in its area, while the concentration of CO in Jrakah intersection are affected by the volume of vehicles passing through, humidity, temperature, wind speed and direction at the intersection itself. The concentration of CO in the area of the factory is not affected by the volume of vehicles passing through, humidity, temperature, wind speed and direction at the Jrakah intersection, and so the concentration of CO in the intersection Jrakah are not affected by the volume of fuel, humidity, temperature, wind speed and direction in the factory area.